The Soviet economy : a book of readings - Bornstein, Morris; Fusfeld, Daniel Roland (Homewood, Ill. : R. D. Irwin, 1962)
This is an introduction to the Soviet economy. The first part, Basic Features of the Soviet Economy embraces the Marxian heritage and the economic mechanism in general; the second (and largest) section deals with industrial planning, consumption and incentives, and the special problems of agriculture and foreign trade; a group of papers on growth follows, and the book ends on the theme Problems and Perspectives.
Includes bibliographical footnotes.
lje 03/10/2018
Loans
Keywords: Economic development; Economic growth; Soviet Union